Absorption, metabolism and elimination of N,N-dimethylformamide in humans - Mráz, J; Nohová, H (International archives of occupational and environmental health, 1992)
Excretion of N,N-dimethylformamide (DMF) and DMF metabolites N-hydroxymethyl-N-methylformamide ("MF"), N-hydroxymethyl-formamide ("F") and N-acetyl-S-(N-methylcarbamoyl)cysteine (AMCC) has been monitored in the urine of volunteers during and after their 8-h exposure to DMF vapour at a concentration of 10, 30 and 60 mg.m-3. The pulmonary ventilation in these experiments was typically about 10 l.min-1 and the retention in the respiratory tract was 90%. After exposure to 30mg DMF.m-3, the yield of compound determined in the urine represented 0.3% (DMF), 22.3% ("MF"), 13.2% ("F") and 13.4% (AMCC) of the dose absorbed via the respiratory tract. The excretion curves of the particular compounds attained their maximum 6-8h (DMF), 6-8h ("MF"), 8-14h ("F") and 24-34h (AMCC) after the start of the exposure. The half-times of excretion were approximately 2, 4, 7 and 23 h respectively. In contrast to slow elimination of AMCC after exposure to DMF, AMCC was eliminated rapidly after AMCC intake. This discrepancy could be explained by rate-limiting reversible protein binding of a reactive metabolic intermediate of DMF, possibly methylisocyanate.
Keywords: Acetylcysteine; Male; Solvents; plíce; Dimethylformamide; rozpouštědla; acetylcystein; Adult; dospělí; mužské pohlaví; Lung; dimethylformamid; lidé; ženské pohlaví; Humans; Formamides; formamidy; absorpce; Absorption; Female; lidé středního věku; Middle Aged